2022
DOI: 10.3390/su14159539
|View full text |Cite
|
Sign up to set email alerts
|

Decentralized Cooperative Active Power Control for Small-Scale Grids with High Renewable Penetration through VSC-HVDC

Abstract: Rising renewable penetration has accelerated the volatility and instability of the power grid. A small-scale grid is especially vulnerable. Therefore, flexibility and stability enhancement are required for small-scale grids. The interconnection with the large-scale grid through the voltage sourced converter-high voltage direct current (VSC-HVDC) can be a solution to the aforementioned problems. VSC-HVDC can deliver power bidirectionally and change the direction in a short time. Hereby, the cooperative operatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The authors in [52] have suggested a decentralized control strategy based on power and frequency relationships. The system consists of three converters connected to the mainland and renewable energy sources (RES).…”
Section: ) Decentralized Cooperative Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors in [52] have suggested a decentralized control strategy based on power and frequency relationships. The system consists of three converters connected to the mainland and renewable energy sources (RES).…”
Section: ) Decentralized Cooperative Controlmentioning
confidence: 99%
“…Central unit [5] Local measurement [52] Communication links [61] Operation Optimal and efficient [20] Optimal with limit [55] Optimal [62] Central Controller Dependent [5] Independent [52] Independent [59]…”
Section: Lc Control Bymentioning
confidence: 99%